Definition of major bleeding: Prognostic classification. (11th September 2020) - Franco, Laura; Becattini, Cecilia; Beyer‐Westendorf, Jan; Vanni, Simone; Nitti, Cinzia; Re, Roberta; Manina, Giorgia; Pomero, Fulvio; Cappelli, Roberto; Conti, Alberto; Agnelli, Giancarlo
Abstract: Background: In patients on anticoagulant treatment, the major bleeding (MB) definition released by the International Society of Thrombosis and Haemostasis (ISTH) is widely accepted. However, this definition identifies MBs with highly variable short‐term risk of death. Objectives: The study aims were to derive and validate a classification of ISTH‐defined MBs for the risk of short‐term death. Methods: Consecutive patients admitted for ISTH‐defined MB occurring while on treatment with oral anticoagulants were included in the study and divided into a derivation and a validation cohort. Death within 30 days was the primary study outcome. Results: Among 1077 patients with MB, 64/517 and 63/560 patients in the derivation and validation cohort died, respectively. In the derivation cohort, Glasgow coma scale (GCS) <14 and shock were predictors of death; critical site bleeding and hemoglobin decrease ≥2 g/dL, or transfusion ≥ 2 units were not. GCS <14 (hazard ratio [HR], 8.67; 95% confidence interval [CI], 3.93‐19.13) was predictor of death in intracranial hemorrhage (ICH) and shock at admission (HR, 4.84; 95% CI, 2.01‐11.70) and pericardial bleeding (HR, 11.37; 95% CI, 1.33‐97.31) in non‐ICH MBs. The predictive value of GCS <14 in ICH and shock and pericardial bleeding in non‐ICH MBs was confirmed in the validation cohort. None of the patients with isolated ocular or articular bleeding died. A prognostic classification of ISTH‐defined MBs for the risk of short‐term death is proposed as "serious, " "severe, " and "life‐threatening" (ICH with GCS <14 or non‐ICH with shock) MBs. Conclusion: According to our study, ISTH‐defined MBs can be stratified for the risk of death within 30 days.